Transforming Arabic Grammar Instruction: A Study on the Effectiveness of Wordwall as an Interactive Learning Tool - Muslih Muslih; Taufik Siraj; Muna Karimatal Mardliyah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
The The media used by teachers when teaching should be able to increase student motivation and learning outcomes, as well as encourage creativity and innovation in learning. Therefore, teachers should not rely solely on conventional media but must be creative in using educational media that can contribute to the learning of Arabic grammar. The rationale behind this study is that teachers still use conventional media despite the rapid development of educational media. Hence, this study aims to determine the effectiveness of using Wordwall educational media on students' Arabic grammar grades. The method used in this study was quantitative with a one-group pretest and posttest approach. The subjects in this study were fifth-grade students at Madrasah Ibtidaiyah Masdarul Ilmi Mojokerto. The sample consisted of 20 students. The instrument used by the researcher was a written test. Data analysis techniques used a paired sample t-test using SPSS version 22. The hypothesis was H0 = there was no improvement from the pre-test to the post-test results after the treatment, and H1 = there was an improvement from the pre-test to the post-test results after the treatment. Based on the results of the paired sample t-test calculation, the probability value sig 0.00 < 0.05, so it can be concluded that H1 is accepted and H0 is rejected, indicating that the wordwall medium can improve nahwu lesson scores and is very effective as a learning medium at Madrasah Ibtidaiyah Masdarul Ilmi Mojokerto